The Effect Of Colchicine on Phenotypes And Stomata Pakcoy (Brassica Rapa L) Hydroponically With The NFT (Nutrient Film Technique) System - nurdiah hasana (Faculty of Science and Technology Universitas Islam Negeri Raden Fatah Palembang, 2020)
Colchicine (C22H25O6N) is a toxic alkaloid compound that causing a polyploidy in the plants, so it produces a robust individuals. The aims of this research are to know the effect of kolchhisin against phenotypes and stomata pakcoy (Brassica rapa L) hydroponically with the NFT (Nutrient Film Technique) system. This research used experimental method with a complete random design (CRD), five treatments and five replications. The data were analyzed by using ANAVA with 5% of credibility. The sample of this research were used pakcoy red arrow F1 nauli with colchicine P0 (Control), P1 (250 mg / L), P2 (500 mg / L), P3 (750 mg / L), P4 (1000 mg / L). The result of this study showed that the influence of colchisin against phenotype and the stomata’s size of pakcoy plant (Brassica rapa L). The high concentrations of colchicine can caused the size of the phenotype (leaves’ number, leaf area, wet weight, dry weight) pakcoy smaller than the control. While the size of the stomata increased, the largest of stomata size was found in the P3 treatment (750 mg / L).